Manual de funciones, valuación de puestos por puntos y reglamento de admisión y empleo para el talento humano de la empresa “Necusoft Cia Ltda (Nettplus) de la ciudad de Loja - Aleaga Trujillo, Doménica Carolina (2017)
uman Talent, within a company, in a highly competitive world, we consider that it is a strategic organizational resource for the achievement of the objectives, emphasizing that it is managed with the People, seeing them as active and proactive agents endowed with intelligence, creativity and skills Intellectuals and others. The present research project had as general objective to realize a "Manual of functions, valuation of points by points and Regulation of admission and employment for the Human Talent of the company NECUSOFT CIA. LTDA. NETTPLUS of the City of Loja ", the same one that allows to contribute with the human talent of the company in several aspects like the fulfillment of the functions of each position, the appropriate techniques for the recruitment of personnel, a fair and according to the allocation of salaries and Finally a correct evaluation of the performance of the personnel and also there were several specific objectives on which the development of the present investigation is based. The methodology used during the present research project is summarized in the use of the following methods: Historical Method, Deductive Method, Inductive Method, Analytical Method and Statistical Method; Also used some research techniques such as: Direct Observation, Interview and Survey, which were used to find and verify with certainty the problems that the company is going through and with this methodology used began Analyze each of the data collected. Within the main aspects in which the present research work was divided we have: In the first instance is the Proposal of the Manual of Functions the same one that in its content describes the suitable profile for each one of the positions taking into account: the identification of the position, the nature of the position, typical functions, responsibilities, abilities and skills, Minimum requirements, working conditions, which requires each job profile. In the second instance regarding the valuation of positions due to the nonconformity of the employees in terms of their remuneration, the system of valuation of positions by points was applied with their respective stages, fixing the points for the grades such as: Education, Experience, Initiative, Responsibility per person, Responsibility for Team, Physical Effort, Mental Effort, Risks and establishing the corresponding score for each of the positions of the company which gave us: Manager 265, Secretary 165, Accountant 190, Chief Administrative Assistant 265, Chief Technical Support 255, Sales Manager 240, Sales Clerk 170, Receptionist 145, Cashier 160, Advertising and Marketing Assistant 205, Telecommunication Assistant 180, Warehouse Operator 165, Warehouse Assistant 215 and Cleaning Assistant 150; Once the weighting was assigned to each of the positions, a summation was obtained in which the following results were obtained: the total of points according to the valuation is 2,770, while the total of the salaries received by the employees is 12,243, 29 with these data we applied the equation of the straight line which gave us as a result 4,83 based on the aforementioned value was made the salary adjustment with a valuation value of 4.42 in order to determine new wages. It should be noted that this revaluation was made only to the positions that were below the salary line that totaled 10 and are: Salesman, Accountant, Financial Administrative Chief, Salesman, Receptionist, Cashier, Advertising and Marketing Assistant, Assistant Telecommunication Operator, Warehouse Operator, Warehouse Assistant and Cleaning Assistant. And to finish with the proposal after having analyzed that the personnel who work in the company has entered the same by relatives or recommendations, without the experience and knowledge needed for each of the positions; A Regulation of Admission and Employment was made the same one that consists of four phases that are: Recruitment, Selection, Contracting, Induction the same ones that are divided in chapters and articles according to the Law it requests the same that they will contribute and they will allow to the company Select the most suitable staff for the different posts required today or in the future. These are the most relevant conclusions that: The company does not have a manual of functions that exposes and clarifies the tasks that must be performed in each one of the positions, which generates disinformation at the moment of performing in the same. It was also known that there are employees who do not have the profile indicated for the position they play within the company. According to the percentage of employees who are not satisfied with their salary, a valuation of positions was made in which it was noted that a large number of positions need u.